2007
DOI: 10.1590/s1413-80502007000400004
|View full text |Cite
|
Sign up to set email alerts
|

Um estudo multinível sobre as filas para internações relacionadas com a gravidez, o parto e o puerpério no SUS

Abstract: Um estUdo mUltinível sobre as filas para internações relacionadas com a gravidez, o parto e o pUerpério no sUsAlexandre Marinho § Simone de Souza Cardoso ¤ resUmo Avaliamos os tempos de espera no Sistema Único de Saúde Brasileiro -SUS, para as internações relacionadas com o capítulo XV (gravidez, parto e puerpério) da CID-10 para os anos de 1999 e 2002. Primeiramente, estimamos os tempos de espera para atendimento com o auxílio de modelos de teoria das filas. Os tempos de espera são longos e elásticos em relaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…This study demonstrated the complexity of the political interactions, which make the successful experiences of the hub municipality city unable to cross borders to its surroundings. The situation ends up negatively impacting the metropolitan health system itself, as it allows access to users who should be cared for in their own municipalities by emergency care, and especially aggravates clinical conditions that could be resolved much earlier and with utmost respect and dignity for the citizens 5,6,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrated the complexity of the political interactions, which make the successful experiences of the hub municipality city unable to cross borders to its surroundings. The situation ends up negatively impacting the metropolitan health system itself, as it allows access to users who should be cared for in their own municipalities by emergency care, and especially aggravates clinical conditions that could be resolved much earlier and with utmost respect and dignity for the citizens 5,6,21 .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the municipalities in the group with optimal living and health conditions were those that offered greater access to health services both in primary care and in specialized care. Studies such as the National Survey by Household Sample (PNAD) of 1998, 2003 and 2008, have reported that people living in more developed regions use more health services than those living in less favored areas 8,19,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The waiting time for a woman to receive healthcare plays an important role during puerperal pregnancy, on the health of pregnant women, mothers and newborns [11]. Research indicates that a waiting period of up to 6 h is considered clinically feasible to keep the prognosis unchanged [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…No hay cargos financieros asociados al uso del sistema público. Sin embargo, porque el sistema público excluye ciertos aspectos de la atención de salud (ocké-Reis, Silveira y Andreazzi, 2002) o si la calidad (Costa y García, 2003), la accesibilidad y el tiempo de espera (Marinhol y Cardoso, 2007) de los prestadores públicos son inadecuados, es posible que las familias prefieran gastar más dinero en prestadores privados y seguro de salud privado (Ribeiro, Barata y otros, 2006;Bós, 2007). La expansión de los planes de salud privados en Brasil durante las décadas de 1980 y 1990 estuvo relacionada por lo menos parcialmente con la mala calidad de los servicios de los proveedores públicos (Alves y Timmins, 2003), la que se deterioró durante la década de 1980 luego de una serie de crisis económicas, crecimiento económico lento y escasez de recursos públicos (Malta, Cecílio y otros, 2004).…”
Section: Introductionunclassified